2017
DOI: 10.3390/v9060127
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Approaches to Assess Bacteriophages in Various Environmental Niches

Abstract: Bacteriophages are ubiquitous and numerous parasites of bacteria and play a critical evolutionary role in virtually every ecosystem, yet our understanding of the extent of the diversity and role of phages remains inadequate for many ecological niches, particularly in cases in which the host is unculturable. During the past 15 years, the emergence of the field of viral metagenomics has drastically enhanced our ability to analyse the so-called viral ‘dark matter’ of the biosphere. Here, we review the evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 171 publications
(215 reference statements)
0
94
0
2
Order By: Relevance
“…There are various studies, which advocate the importance and focused on the exploration of virome and phages from diverse sources [3, 14, 82-87]. However, to best of our knowledge, there is no metagenomic study reported that explore phage diversity from the Ganges River since the discovery of phages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are various studies, which advocate the importance and focused on the exploration of virome and phages from diverse sources [3, 14, 82-87]. However, to best of our knowledge, there is no metagenomic study reported that explore phage diversity from the Ganges River since the discovery of phages.…”
Section: Discussionmentioning
confidence: 99%
“…Phages also have evolutionary impact as they can facilitate recombination event, integration as prophages etc. [10, 14]. Furthermore, they are also effective alternative to antibiotics and can be utilized as therapy [15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…And finally, it leaves viruses invisible because of the absence of a universally conserved marker gene in their genome. (10) A second approach is to sequence the whole genome of all the species in the microbiome. (9) While whole-genome sequencing does not suffer from the same problems such as amplification bias and intrinsic preclusion of viruses, the most common sequencing techniques are unable to deliver both long sequence-reads and high-throughput.…”
Section: Introductionmentioning
confidence: 99%